Introduction to Quantum Harmonic Oscillator Material Using Discussion Method for Students of SMAN 5 Bengkulu City - Iwan Setiawan; Mayasari Katrina Hutagalung; Nurhasanah Nurhasanah; Dedy Hamdani (DIKDIMAS : Jurnal Pengabdian Kepada Masyarakat, 2023)
The knowledge of the student about harmonic oscillators is quite limited. The purpose of this PPM is to 1) increase the knowledge of Bengkulu City 5 SMAN students about Quantum Harmonic Oscillators and their application in everyday life 2) improve the skills of Bengkulu City 5 High School students in calculating Quantum Harmonic Oscillators using the fast-forward method to accelerate quantum dynamics adiabatic. PPM was carried out at SMAN 5 Bengkulu City, especially in class 12 IPA 5 on October 24, 2022. The research method was carried out in three stages. The first stage is preparation. The second stage is the presentation of quantum harmonic oscillator material using research instruments in the form of power points, the third stage is research evaluation.